2020
DOI: 10.26434/chemrxiv.12252059.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanically-Tunable Quantum Interference in Ferrocene-Based Single-Molecule Junctions

Abstract: Ferrocenes are ubiquitous organometallic building blocks that comprise a Fe atom sandwiched between two cyclopentadienyl (Cp) rings that rotate freely at room temperature. Of widespread interest in fundamental studies and real-world applications, they have also attracted<br>some interest as functional elements of molecular-scale devices. Here we investigate the impact of<br>the configurational degrees of freedom of a ferrocene derivative on its single-molecule junction<br>conductance. Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…1-25) (Fig. 5c) [4][5][6][7][8][9][10]46,47,[51][52][53] . It is reported that the para-polyphenylenes can have a conductance enhancement of one order of magnitude by changing the tilted angles attaching the gold electrode 8,9 .…”
Section: General Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…1-25) (Fig. 5c) [4][5][6][7][8][9][10]46,47,[51][52][53] . It is reported that the para-polyphenylenes can have a conductance enhancement of one order of magnitude by changing the tilted angles attaching the gold electrode 8,9 .…”
Section: General Characterizationmentioning
confidence: 99%
“…The alkanes 5 , silanes 6 , and other linear systems with cis-trans isomers are common structures used as mechanical triggered switches because their conductance can be modulated by mechanical force via the deformation of the flexible alkane chains or cis-trans isomerization. The switching factor, defined as the ratio of the conductance of the highest conductance state to that of the lowest conductance state, is an important parameter to quantify modulation ratio 5,7 . The most-reported molecules usually have low mechanical switching factors~10 [4][5][6][7] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical control of destructive QI is also thought to be responsible for the large conductance fluctuations seen in experiments on ferrocene-based molecular wires (Camarasa-Gómez et al, 2019). In this case, the proposed effect derives from a rotational degree of freedom that can switch the junction's QI from destructive to constructive and back.…”
Section: Quantum Interferencementioning
confidence: 99%
“…This behavior has been taken as a hallmark in the experimental discovery of the FCB. In the context of nanoscale devices, the FCB was first observed in carbon nanotubes (Leturcq et al, 2009), where the blockade survives over several charge states N. A molecular FCB was first observed by Burzurí et al (2014) in an Fe 4 complex. The FCB has some remarkable consequences for the charge-carrier dynamics (Koch, von Oppen, and Andreev, 2006).…”
Section: J Franck-condon Blockadementioning
confidence: 99%